Direct comparison of the novel automated screening tool (AST) versus the manual screening tool (MST) in patients with already implanted subcutaneous ICD. (15th August 2018) - Bögeholz, Nils; Pauls, Paul; Güner, Fatih; Bode, Niklas; Fischer, Alicia; Dechering, Dirk; Frommeyer, Gerrit; Köbe, Julia; Wasmer, Kristina; Eckardt, Lars; Reinke, Florian
Abstract: Background: The subcutaneous implantable cardioverter–defibrillator (S-ICD) has evolved as a valuable alternative to the transvenous ICD, especially in young patients. Unfortunately, some of these patients are ineligible for S-ICD implantation due to specific electrocardiographic features. So far, these patients were identified by mandatory pre-implantation screening using the manual screening tool (MST), which lacks objective value. Therefore, a novel automated screening tool (AST) has been introduced recently for objective screening, which has not been evaluated yet. Methods/results: We here first investigate the novel AST, in direct comparison to MST, in 33 consecutive patients with already implanted S-ICD system to compare predicted eligibility by screening tools with true sensing of the S-ICD system. Both screening tools reliably predicted true ineligible single vectors, but also suggested overall ineligibility in a similar fraction of patients (MST: 3.0%; AST: 6.1%), albeit the implanted S-ICD worked flawlessly in these patients. AST did not predict the finally selected sensing vector better than MST. There was a surprising mismatch between AST and MST for the predicted eligibility of single vectors; only in 49% of patients did both screening tools predict eligibility for the same vectors. Conclusions: The novel AST predicted overall eligibility approximately similar to MST. Both tools predicted ineligibility in a few patients, who were actually eligible. There was a striking mismatch between both screening tools when eligibility of single vectors was predicted. Thus, the AST seems to be a valuable advance, due to its standardized and objective process, but it still lacks specificity. Highlights: The novel AST supplies an objective screening prior to S-ICD implantation. AST approximates to MST when predicting overall eligibility. Similar to MST, AST lacks specificity to identify truly eligible patients. There is a striking mismatch between AST and MST on single vector level. AST did not predict the finally selected vector better than MST.